Evaluation of Pear Deck Application in Learning to Write Poetry Text in Senior High School - Rifa, Sabrina Khoir; Huda, Miftakhul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Interactive technology and applications have been widely used in learning, but studies that comprehensively evaluate their effectiveness through student activity, learning efficiency, learning outcomes, and teacher and student sat-isfaction levels are still limited. This study aims to evaluate the effectiveness of the application of the Pear Deck application in learning to write poetry texts at SMAN 1 Karanganom based on these four aspects. Methodology: The method used in this study is qualitative descriptive with a case study re-search design. Data was collected through interviews, observations, and questionnaires from 35 students in class XI E SMAN 1 Karanganom, Klaten. Data analysis was carried out based on five stages according to John W. Cre-swell and J. David Creswell: (1) preparing the data, (2) displaying the data, (3) encrypting the data, (4) compiling descriptions and themes, and (5) pre-senting the results. Data validity is guaranteed through triangulation of tech-niques and sources. Results: The results of the study show that students are active during the learning pro-cess, with good interaction between peers and teachers. Learning runs effi-ciently because all students can complete the exercises on time. As many as 74% of students obtained a score in the good category, and 26 out of 35 stu-dents expressed satisfaction with the use of the Pear Deck application in learning to write poetry. Applications/Originality/Value: This research provides new insights in evaluating technology-based learning as a whole using four main aspects. These findings are useful for teachers in starting the effectiveness of learning technology.